1985
DOI: 10.1507/endocrj1954.32.635
|View full text |Cite
|
Sign up to set email alerts
|

Manganese ion as a goitrogen in the female mouse.

Abstract: Effect of excessive ingestion of manganese (Mn) on the mouse thyroid was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…There was a clear sex-specific difference in the phenotype of Slc30a10 Ϫ/Ϫ mice; thyroxine levels and normalized body weights were lower in males. Sex-specific differences in the effects of manganese on thyroid function were also described in the report by Kawada et al (41). Unlike our study, in that of Kawada et al (41), female mice were sensitive.…”
Section: Figure 5 Measurements Of Additional Anterior Pituitary Hormsupporting
confidence: 74%
See 2 more Smart Citations
“…There was a clear sex-specific difference in the phenotype of Slc30a10 Ϫ/Ϫ mice; thyroxine levels and normalized body weights were lower in males. Sex-specific differences in the effects of manganese on thyroid function were also described in the report by Kawada et al (41). Unlike our study, in that of Kawada et al (41), female mice were sensitive.…”
Section: Figure 5 Measurements Of Additional Anterior Pituitary Hormsupporting
confidence: 74%
“…In 1983, the same authors (40) demonstrated that rats treated with manganese for a longer period (1 mg MnSO 4 ⅐H 2 O/100 g daily for 5 weeks) had decreases in body weight, and serum thyroxine and thyroid-stimulating hormone levels. In 1985, Kawada et al (41) reported that ingestion of 200 mg/liter MnCl 2 ⅐4H 2 O for 7 weeks induced goiter in female mice. In that study, manganese-treated animals also exhibited a mild reduction in serum thyroxine levels (41).…”
Section: Figure 5 Measurements Of Additional Anterior Pituitary Hormmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of plasma manganese were elevated in individuals with goiter in another study (49). In rodents, administration of manganese was reported to reduce serum levels of thyroxine or induce goiter (42,50,51). Thus, there is precedent for our discovery of manganese-induced thyroid defects in Slc30a10 knockout mice.…”
Section: Zip14 Depletion Rescues Hypothyroidism In Slc30a10 Knockoutsmentioning
confidence: 98%
“…The authors concluded that manganese uptake by the thyroid is controlled by serum TSH and thyroid hormone concentrations. Another study examined the role of manganese in goiter development (Kawada et al, 1985). Mice were fed excessive amounts of manganese while iodine concentrations in the diet remained at normal levels.…”
Section: Manganese Thyroid Hormone and Dopamine 3a Manganese And Thmentioning
confidence: 99%